Surface Modification of Aliphatic Polyester to Enhance Biocompatibility - Bu, Yazhong; Ma, Junxuan; Bei, Jianzhong; Wang, Shenguo (Frontiers in Bioengineering and Biotechnology, 2019)
Aliphatic polyester is a kind of biodegradable implantable polymers, which shows promise as scaffolds in tissue engineering, drug carrier, medical device, and so on. To further improve its biocompatibility and cell affinity, many techniques have been used to modify the surface of the polyester. In the present paper, the key factors of influencing biocompatibility of aliphatic polyester were illuminated, and the different surface modification methods such as physical, chemical, and plasma processing methods were also demonstrated. The advantages and disadvantages of each method were also discussed with the hope that this review can serve as a resource for selection of surface modification of aliphatic products.